The Actions of International Economic Organizations to Solve Global Issues (Texas Journal of Multidisciplinary Studies, 2022)
They arise from the uneven development of various spheres of modern human life and the contradictions that arise in people's socio-economic, political, ideological, socio-natural and other relationships. These problems have a negative and side effect on the life of all mankind